Power and Prejudice: Analyzing the Decline of Parliamentary Democracy in Pakistan, 1955-1958 - Haider, Zulqarnain; Abbas Khan, Dr. Amjad (Al-Amīr Research Journal for Islamic Studies, 2024)
Democracy, since the day of its notion, has become the only game in the town; it is the form of government where people choose their representatives to enjoy its true fruit. Subcontinent has a long history of kingship where most of the rulers came to rule it for certain period of times. Though, the emergence of British East India company in India was the change of masters not only for Hindus but rest of the communities except the Muslims. However, the arrival of British changed the infra-structure of the Sub-Continent. Initial drastic measures, by the colonial masters, installed the new political ideas in the minds of the Indians. Moreover, due to this political consciousness, the Indians were demanding self-rule in India that not only provided an opportunity in power sharing but also introduced democracy in the Sub-Continent on limited scales. At the time of creation of two independent states Pakistan adopted parliamentary democracy as a form of government. Meanwhile, the state’s first experience with democracy did not remain pleasant one and it failed to achieve its true aspirations in late 1950s. This study has attempted to explore the fragile experience of democracy in Pakistan in early phase. Keywords: Parliamentary Democracy, Governance, Leadership, Institutions, Power.